Peningkatan Kesadaran Masyarakat tentang Pencegahan Penyebaran Infeksi Covid 19 - Immawati Immawati; Tri Kesuma Dewi; Ludiana Ludiana; Senja Atika Sari (Fakultas Ilmu Sosial dan ilmu Politik, 2022)
Coronaviruses are a large family of viruses that cause illness ranging from mild to severe symptom. Covid-19 can be transmittted from human to human through close contact and droplets, not through the air. Standar recommendations to prevent the spead of infection are through regular hand washing, apply cough and sneezing etiquette, avoiding close contact with anyone showing symptoms of respiratory illness. Health education on preventing the transmission of the Covid pandemic is one of the effort in preparing the public to understand the dangers of transmitting the Covid-19 virus. This community service activity is aimed for health cadres and mothers participanting in posyandu. The service method uses health education methods. The result of community service show that participation and support from the community and the puskesmas are quite high, where participants are actively involved in the health education provided so that the community can ultimately improve healthy living behavior in preventing the spread of Covid-19 infection.